Does Organizational Support Influence The Nexus Between Role Conflict And The Intentions To Stay On The Job? A Study Among Public Sectors Employees - Prince Addai; Isaac Nti Ofori; Daniel Obeng Acquah; Afia Nyarko Boakye; Esther Asiedu (SEISENSE Business Review)
Even though copious studies have shown that a relationship exists between role conflict and the intention to stay on the job, the mechanisms that curb the relationship between role conflict and intention to stay have not often been explored. This study examined the moderating role of organizational support on the nexus between the components of role conflict and the intention to stay in the organization. Two hundred and eighty-seven (n=287) public sector employees were selected using the cross-sectional survey design for the study. Data was gathered using the Role Conflict Scale, Perceived Organizational Support Scale, and the Intentions to Stay Inventory. Multiple regression was used in analyzing the data. Findings indicated that a significantly negative relationship exists between the two components of role conflict (inter-role and intra-role) and the intentions to stay in the organization. There was a positive nexus between perceived organizational support and the intentions to stay in the organization. The nexus between the two components of role conflict and the intentions to stay in the organization was moderated by perceived organizational support. The results provide some crucial insights for employers on how to inspire employees to stay in the public service. The limitations, recommendations, and implications for future studies have been emphasized.